2015
DOI: 10.1016/j.scitotenv.2015.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Identification of traffic-related metals and the effects of different environments on their enrichment in roadside soils along the Qinghai–Tibet highway

Abstract: • Cr, Zn, Cu, As, Cd, and Pb in soils along the highway are related to the traffic.• There are three distribution patterns of the traffic-related metals in soils.• Regional differences had significant relationship with the enrichment levels.• Cd was the prior metal and the TTH was the key area for soil environment monitoring. The road transportation could affect roadside soils environment detrimentally, including heavy metal enrichment. In order to identify and evaluate the enrichment of heavy metals resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(75 citation statements)
references
References 47 publications
(78 reference statements)
7
67
0
1
Order By: Relevance
“…Furthermore, they speculated that Pb accumulation in the remote high mountains of the eastern Qinghai-Tibet Plateau might be mainly caused by the long distance atmospheric transport. P. Wang et al (2015) observed deficit of Cu & Zn and an enrichment of Pb in the soils from the Qinghai Lake catchment. They pointed out that elements in soils mainly originated from natural sources according to soil geochemical patters, cluster analysis, and principal component analysis, while some human activities also influenced elements in virgin topsoils.…”
Section: Major and Trace Elements In Environmental Media Of The Qinghmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, they speculated that Pb accumulation in the remote high mountains of the eastern Qinghai-Tibet Plateau might be mainly caused by the long distance atmospheric transport. P. Wang et al (2015) observed deficit of Cu & Zn and an enrichment of Pb in the soils from the Qinghai Lake catchment. They pointed out that elements in soils mainly originated from natural sources according to soil geochemical patters, cluster analysis, and principal component analysis, while some human activities also influenced elements in virgin topsoils.…”
Section: Major and Trace Elements In Environmental Media Of The Qinghmentioning
confidence: 94%
“…X. Wang et al (2015) reported TSP concentrations in Lulang of TP, with value of 4.1-46.7 μg/m 3 . TSP concentrations exhibited seasonal patterns with lower levels in summer seasons and higher values in the winterspring season.…”
Section: Air Pollution Of the Qinghai-tibet Plateaumentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern was consistent with previous studies and indicated that the highway was the main source of these contaminants. The study of traffic-related metals in roadside soils along the Qinghai-Tibet highway indicated that Cu, Zn, Pb, Cr, Cd, and As were related to road transportation (Zhang et al 2015) and the contents of Zn, Pb, and Cd in roadside soils decreased exponentially with the distance from the road (Yan et al 2013;Zhang et al 2015). The heavy metal in soil alongside mountain railway in Sichuan showed that the concentrations of Cu, Zn, Mn, Pb, and Cd decreased with increasing distance from the railroad and indicated that railway transport was the source of such pollutants (Liu et al 2009 The third group of metals, Hg and As, indicated that the traffic did not affect both of elements because in this study area, the concentration of Hg and As did not decrease with increasing distance from the highway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, vegetation affected by extreme weather benefits from the ecological reconstruction programs that have been organized from human activity [38]. If human activity such as industrialization and agricultural cultivation continues to increase, the grassland ecosystem is certain to be altered dramatically [39]. In such an eventuality, it will be necessary to take such measures as limiting grazing to minimize the overall impact due to a warming climate.…”
Section: Relationship Between Npp and Climate/humanmentioning
confidence: 99%